Anti-HIV diphyllin glycosides from Justicia gendarussa. (April 2017) - Zhang, Hong-Jie; Rumschlag-Booms, Emily; Guan, Yi-Fu; Liu, Kang-Lun; Wang, Dong-Ying; Li, Wan-Fei; Nguyen, Van Hung; Cuong, Nguyen Manh; Soejarto, Djaja Doel; Fong, Harry H.S.; Rong, Lijun
Abstract: In a search for new anti-HIV active leads from over several thousands of plant extracts, we have identified a potent plant lead. The active plant is determined as Justicia gendarussa (Acanthaceae), a medicinal plant that has been used for the treatment of injury, arthritis and rheumatism in Asia including China. Our bioassay-guided fractionation of the methanol extract of the stems and barks of the plant led to the isolation of two anti-HIV compounds, justiprocumins A and B. The compounds are identified as new arylnaphthalide lignans (ANL) glycosides. We further determined that the ANL glycosides are the chemical constituents that contribute to the anti-HIV activity of this plant. Justiprocumin B displayed potent activity against a broad spectrum of HIV strains with IC50 values in the range of 15–21 nM (AZT, IC50 77–95 nM). The compound also displayed potent inhibitory activity against the NRTI (nucleoside reverse transcriptase inhibitor)-resistant isolate (HIV-11617-1 ) of the analogue (AZT) as well as the NNRTI (non-nucleoside reverse transcriptase inhibitor)-resistant isolate (HIV-1N119 ) of the analogue (nevaripine). Graphical abstract: Two new anti-HIV arylnaphthalide lignan glycosides were isolated from the stems and barks of Justicia gendarussa . Justiprocumin B (2 ) displayed potent inhibition activity against a broad spectrum of HIV-1 strains including the NRTI and NNRTI resistant strains. Highlights: New arylnaphthalide lignan glycosides were identified from Justicia gendarussa. The compounds were isolated through anti-HIV bioassay-guided fractionation. The structures were determined by spectroscopic means including 2D NMR analyses. The isolates from Justicia gendarussa were evaluated against a broad spectrum of HIV-1 strains. The lignan justiprocumin B displayed potent anti-HIV activity with IC50 values in the range of 15–21 nM.